Sensitivity Analysis of Investment and NPV Analysis with Monte Carlo Simulation in Asphalt Mixing Plant (AMP) Industry - Wachid Hasyim; Ayu Krisma Wardani (JURUSAN TEKNIK SIPIL, 2023)
The availability of proper transportation infrastructure in cities / districts with high population growth will support development growth. Development growth can be seen at the growth of the regional economic level, so that economic growth is strongly supported by the development of road transportation facilities. National development in the transportation sector begins with the implementation of roads as infrastructure that strongly supports the achievement of national development goals. Road planning standards state that for road pavement layers must meet certain classifications and specifications. Thus, to be able to meet the needs of materials with adequate quality and quantity, a supporting industry is needed, namely in the form of industry or asphalt mixing plants (AMP). This research is reviewed from the financial aspect which aims to analyze the feasibility of investing in asphalt mixing plants (AMP). Based on the Investment Feasibility Analysis, the NPV (Net Present Value) value is IDR. 30,777,082,259.61, BCR (Benefit Cost Ratio) is 1.39, IRR (Internal Rate of Return) is 30%, PP (Payback Period) is 4.16 years. Based on sensitivity analysis, the value of sensitivity investment at IDR. 73,386,171,697.09. NPV value based on monte carlo simulation with two scenarios obtained values of IDR. 27,553,320,897.33 and IDR. 23,719,088,232.49 respectively.